Graphitic-carbon-nitride-hydrophilicity-dependent photocatalytic degradation of antibiotics with different log Kow - Lee, Jong Min; Lee, Youn Jun; Jeong, Yoo Jae; Cho, In Sun; Jho, Eun Hea; Park, Seong Jik; Lee, Chang Gu (Chemosphere, 2024)
The surface hydrophilicity of a photocatalyst is an important factor that directly influences its interactions with organic pollutants and significantly impacts its degradation. In this study, we investigated the impact of increased hydrophilicity of g-C3N4 (CN) by alkaline solvothermal treatment on the degradations of three antibiotics (oxytetracycline (OTC), oxolinic acid (OA), and sulfamethoxazole (SMX)) with different log Kow values. Scanning electron microscopy (SEM), X-ray diffraction analysis (XRD), and Fourier-transform infrared (FT-IR) spectroscopy showed no significant differences in the morphology, crystalline structure, and surface functional groups of CN after alkaline solvothermal treatment (Nv-HPCN). However, contact angle analysis revealed that Nv-HPCN (31.8°) was more hydrophilic than CN (61.1°). To assess the hydrophilicity of the antibiotics, the log Kow values of SMX (0.77), OA (0.43), and OTC (−0.34) were measured. Nv-HPCN showed faster OTC degradation than CN, whereas the opposite pattern was observed for the degradation of OA. Scavenger tests showed that O2•− and h+ mainly contributed to the degradation of these antibiotics. Furthermore, the influences of NOM and coexisting anions on antibiotic degradation were investigated. This study thus offers perspectives on the impact of surface hydrophilicity of photocatalysts on the degradation of antibiotics.
Keywords: Alkalines; Crystalline surfaces; G-C3N4; Graphitic carbon nitrides; Nitrogen vacancies; Oxolinic acid; Photocatalytic degradation; Solvothermal treatment; Sulfamethoxazole; Surface hydrophilicity; Anti-Bacterial Agents; Catalysis; Graphite; Nitrogen Compounds; Oxytetracycline; Spectroscopy, Fourier Transform Infrared; Antibiotic; g-C3N4; Hydrophilicity; Nitrogen vacancy; Photocatalysis